The role of lipoteichoic acid on amyloidogenesis and its effect on erythrocytes and platelets - Nkosi, Nondumiso Belvia (Stellenbosch : Stellenbosch University, 2019)
Thesis (MSc)--Stellenbosch University, 2019.